ABOUT THE IMPORTANCE OF ETIQUETTE IN THE PEDAGOGICAL SPHERE - Ibragimova, Dilbar; Kuvandikova , Mohinabonu; Burkhanova, Mamura (Innovative Development in Educational Activities, 2022)
The discipline "Professional Ethics" is important in the formation of future teachers’ pedagogical ethics because it includes not only the study of theoretical foundations of professional and pedagogical ethics, but also the analysis of relevant regulatory documents such as the code of professional ethics of the teacher, the ethical code of the teacher, the code of honor and service of the teacher, the professional code ethics and official behavior of a teacher, and so on. Professional regulatory materials should illustrate to students the requirement to conform with ethical standards and rules of behavior in order to enter the professional community and, more importantly, for professional growth.